2019
DOI: 10.1177/2158244019833880
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and Factors Influencing Parent–Child Communication About HIV/AIDS, and Sexual and Reproductive Health Issues in Nigeria

Abstract: Background and Rationale Since the outbreak of HIV/AIDS in the early 1980s (AVERT, 2018), efforts have been consistent to curtail its spread. Unscreened blood transfusions, sharing unsterilized needles and syringes among injecting drug users (IDUs), indiscriminate sexual behaviors, limited knowledge and poor perception of HIV/AIDS, concealment of symptoms for fear of stigmatization, and poverty are key spread factors of the deadly virus (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 25 publications
0
6
1
Order By: Relevance
“…The reason may be associated with differences in culture, socioeconomic development and studied populations, whereby the study in Zambia included adolescents of highly educated families. In this study, PAC on SRH issue was higher than studies conducted in different regions of Africa (Ojebuyi et al , 2019; Bushaija et al , 2013; Muthengi et al , 2015). The discrepancies may be resulted from gaps in study area and period, number of dimensions and timing used to definePAC and differences in the source populations of the study.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…The reason may be associated with differences in culture, socioeconomic development and studied populations, whereby the study in Zambia included adolescents of highly educated families. In this study, PAC on SRH issue was higher than studies conducted in different regions of Africa (Ojebuyi et al , 2019; Bushaija et al , 2013; Muthengi et al , 2015). The discrepancies may be resulted from gaps in study area and period, number of dimensions and timing used to definePAC and differences in the source populations of the study.…”
Section: Discussioncontrasting
confidence: 66%
“…PAC on SRH issues varies across and within countries. It reached to 71% in USA (Widman et al , 2014), 21% in Tanzania (Muthengi et al , 2015), 9.5% in Nigeria (Ojebuyi et al , 2019), 90% in Zambia (Haakonde et al , 2018), 61% in Ghana (Esantsi et al , 2015) and 19% in Rwanda (Bushaija et al , 2013). In Ethiopia, PAC on SRH matters among secondary and preparatory school students varied by setups like 47% Oromia (Habte et al , 2019), 28.9% in BenishangulGumuz (Yesus and Fantahun, 2010), 68.5% (Mekie et al , 2019) and 82.7% in Amhara region (Chane and Cherie, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…12 In corroboration, a study carried out in Nigeria revealed that the prevalence of communication between parents and children is low on SRH topics such as HIV/AIDS, family planning, and contraception, at 37.4%, 32.5%, and 9% respectively. 26 Similarly, another study conducted in Ebonyi State, Nigeria also revealed that the majority of adolescents never discussed anything related to sex with their parents or caregivers but discussed it with their friends or peers. 27 The similarities in these studies may be due to the barriers associated with parent-adolescent sexuality communications.…”
Section: Discussionmentioning
confidence: 98%
“…However, the study shows family and friends playing a lesser role in the provision of information. This may indicate the cultural, religious and other taboos which limit open discussion of SRH matters between parents and their children [58][59][60][61]. In South Africa, families who openly discuss SRH issues with their children are in the minority [60].…”
Section: Respondents' Sources Of Informationmentioning
confidence: 99%